STRATEGI PENGEMBANGAN PEMASARAN DIGITAL TERHADAP UMKM M_TWO CAPCAY SOLO - Melissa Lestari (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Digital marketing is an effort to promote brands or products online that can be used by MSMEs to reach consumers and potential clients quickly and effectively to increase sales. UMKM M_TWO Capcay Solo is an UMKM that focuses on seafood. While running their business, UMKM M_TWO has never used social media as content marketing. Therefore, the author intends to help optimize M_TWO MSME content marketing via social media. The author's data collection method utilizes interview techniques by asking several questions that the author can use to develop the stages of digital transformation ideas in M_TWO MSMEs. The results obtained during the assistance from the use of social media show that there is engagement with M_TWO content and M_TWO owners also understand how to properly market their products on social media and already have social media accounts such as Mailchimp, Linktree, Facebook, Instagram, Whatsapp Business, as well as content drafts that the author helps make for future social media marketing.